2017
DOI: 10.1016/j.scitotenv.2017.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Examining global electricity supply vulnerability to climate change using a high-fidelity hydropower dam model

Abstract: An important and plausible impact of a changing global climate is altered power generation from hydroelectric dams. Here we project 21st century global hydropower production by forcing a coupled, global hydrological and dam model with three General Circulation Model (GCM) projections run under two emissions scenarios. Dams are simulated using a detailed model that accounts for plant specifications, storage dynamics, reservoir bathymetry and realistic, optimized operations. We show that the inclusion of these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(79 citation statements)
references
References 41 publications
1
78
0
Order By: Relevance
“…The approach involves forcing a hydrological model with gridded GCM temperature and precipitation projections to determine runoff, which is then routed to estimate streamflow at hydropower dams of interest. This method has been employed and validated in previous global studies (e.g., [5,34]; here the inclusion of a detailed hydropower database for Brazil allows for a far more comprehensive assessment for this particular country. The following steps were taken.…”
Section: Hydrological Modelmentioning
confidence: 99%
“…The approach involves forcing a hydrological model with gridded GCM temperature and precipitation projections to determine runoff, which is then routed to estimate streamflow at hydropower dams of interest. This method has been employed and validated in previous global studies (e.g., [5,34]; here the inclusion of a detailed hydropower database for Brazil allows for a far more comprehensive assessment for this particular country. The following steps were taken.…”
Section: Hydrological Modelmentioning
confidence: 99%
“…This represents a great barrier to performing effective integrated assessment studies, developing modelling frameworks, and recommending policies for resilience building. While a multitude of studies have been carried out at the basin or global scale in terms of assessing the projected long-term impacts of climate change on hydropower generation potential [13][14][15][16][17][18] and on the discharge of rivers [19], only few have assessed the impact of hydro-climatic extreme events on power supply reliability [20][21][22] and the related impacts on electricity consumption. Moreover, researchers (see [23]) have recently highlighted the necessity of reconciling top-down and bottom-up approaches to climate and energy-related assessment, indicating that novel methodologiesincluding the use of earth observation data [24,25]are required.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that the spatiotemporal patterns of water resources are expected to shift under conditions of climate change, especially in snow-dominated regions because of the near-surface warming caused by increased greenhouse gas emissions (Barnett et al 2005, Hamlet et al 2010, Van Rheenen et al 2004. The non-stationarity of water resources availability induced by climate change will directly affect potential future hydropower production (Hamududu and Killingtveit 2012, Kao et al 2015, van Vliet et al 2016, Turner et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been adopted in many large-scale energy assessment studies based on regulated or even natural runoffs (e.g. Lehner et al 2005, van Vliet et al 2013, Liu et al 2016, Turner et al 2017. This simple process-based model provides the total potential hydropower generation that could be used for both reserve and generation services to the electric grid.…”
Section: Introductionmentioning
confidence: 99%